THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY (CSR) DISCLOSURE AND FINANCIAL PERFORMANCE ON COMPANY VALUE IN CONSUMER GOODS COMPANIES THAT GO PUBLIC ON THE BEI - Anatasya Trisandy; Eka Nuraini; Dedek Sri Wahyuni (International Conference On Law And Social Sciences, 2024)
The aim of this research is to analyze The Effect of Corporate Social Responsibility (CSR) Disclosure and Financial Performance on Company Value in Consumer Goods Companies that Go Public in Bei. The population in this research is all industrial companies in the Consumer Goods sector listed on the Indonesia Stock Exchange. By using Purposive Sampling techniques, a sample of 32 companies was obtained. The type of data used is secondary data obtained from the company's annual report on the Indonesian stock exchange and the company's official website. The data analysis technique used in this research is Multiple Regression Analysis. The research results show that all independent variables simultaneously influence company value. However, partially the Corporate Social Responsibility (CSR) variable, Return on Assets (ROA), has a positive and significant effect on company value, while Return on Equity (ROE) has no effect on company value.